When a virtual museum is too good: the curiosity satisfaction paradox and its implications for the substitution effect of virtual technology - Abdulrazak, Saleh; Mohd Kamal, Othman; Sabine Chung, Sze Yee; Ahmad Azaini, Abdul Manaf; Shaziti, Aman; Mohamad Hardyman, Barawi (Elsevier B.V., 2026)
This mixed-methods study evaluates the strategic efficacy of digital museum platforms by comparing a traditional museum website with a VR-only app and a VR-gamified app. Ninety participants were randomly assigned to one platform, after which they completed the System Usability Scale (SUS) and Museum Experience Scale (MES); semi-structured interviews provided crucial qualitative depth. Our quantitative findings reveal a significant difference in usability, with the VR-gamified app outperforming the website (χ2(2) = 9.778, p = 0.001676), indicating a medium effect size (∊2 = 0.110). However, the VR-only app was not significantly different from the website (p = 0.09174). Additionally, gamification did not significantly enhance the museum experience over the VR-only app, suggesting a potential ceiling effect of VR immersion. Critically, qualitative insights revealed a novel “curiosity satisfaction paradox”: while both VR apps significantly influenced participants’ pre-visit intentions and willingness to share, demonstrating a compelling “teaser” effect, the comprehensive VR-gamified experience surprisingly satisfied the curiosity of some users, reducing their motivation for a physical visit. This study underscores the need for a nuanced strategic approach to ensure digital platforms effectively complement, rather than inadvertently substitute for, the physical museum experience.